2023
DOI: 10.2147/jir.s413374
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Cordyceps sinensis and Its Fermented Mycelium Products on Ameliorating Renal Fibrosis by Reducing Epithelial-to-Mesenchymal Transition

Abstract: Renal fibrosis is a hallmark and common outcome of various chronic kidney diseases (CKDs) and manifests pathologically as accumulation and deposition of extracellular matrix (ECM) in the kidney. Epithelial-to-mesenchymal transition (EMT) has been shown to be an important mechanism involved in renal fibrosis. Cordyceps sinensis, a traditional Chinese medicine, has long been used for the treatment of renal fibrosis. As research on the mycelium of C. sinensis progressed, a variety of medicines developed from ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…For the parts that have not yet been studied, we can further verify and explore through in vivo and in vitro experiments. (Zhao-Long et al, 2000;Pan et al, 2013;Du et al, 2015;Song et al, 2016;Takakura et al, 2017;Xiao et al, 2018;Zheng et al, 2018;Wang et al, 2019;Cai et al, 2021;Zhang et al, 2023a;Zhang et al, 2023b).…”
Section: Go Bioanalysis and Kegg Enrichment Analysismentioning
confidence: 99%
“…For the parts that have not yet been studied, we can further verify and explore through in vivo and in vitro experiments. (Zhao-Long et al, 2000;Pan et al, 2013;Du et al, 2015;Song et al, 2016;Takakura et al, 2017;Xiao et al, 2018;Zheng et al, 2018;Wang et al, 2019;Cai et al, 2021;Zhang et al, 2023a;Zhang et al, 2023b).…”
Section: Go Bioanalysis and Kegg Enrichment Analysismentioning
confidence: 99%
“…Mycelium has good flavor, high-quality protein, and essential micronutrients that bring benefits to public health [ 15 ]. The mycelium of Cordyceps sinensis , obtained by fermentation, has been widely used in developing various drugs, mainly for treating chronic kidney disease [ 16 ]. Lu et al found through animal experiments that the mycelia of Antrodia camphorata and Armillariella tabescens have protective effects on the liver [ 17 ].…”
Section: Introductionmentioning
confidence: 99%